Exploring the characteristics of an optimal design of digital materials for concept learning in mathematics: Multimedia learning and variation theory - Chiu, Thomas K.F.; Churchill, Daniel (Computers and education, 2015)
Design principles emerging from the cognitive theory of multimedia learning can be applied to engage cognitive processing, and teaching methods that have evolved from variation theory can encourage thinking through comparisons in mathematics education. Applying these principles and teaching methods in designing digital material should be a sound proposition. However, there is a disconnection between research in digital educational material and classroom practices. Teachers often have doubts about the effectiveness of the materials. Thus, this paper presents a design-based research of developing a digital material for algebra concept learning. We collaborated with two experienced teachers and a subject expert from a university, and designed some digital learning material that was presented to 68 students through an iterative redesign development cycle; the effectiveness of the final product was tested on another group of 66 students the following year. Characteristics of an optimal design generated from the data collected are presented in this paper. The characteristics may have useful practical implications for instructional designers and teachers and contribute to improvements in the design of digital learning materials. •Multimedia learning principles (MLP) engage cognitive processing.•Applying variation theory (VT) in mathematics education is promising.•Collaborating with practitioners is an appropriate methodology.•An iterative redesign cycle was adopted to investigate how to apply VL and MLP.•Characteristics of an optimal design for concept learning are suggested.